2018
DOI: 10.3899/jrheum.171306
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Intraarticular Heterotopic Bone Formation in the Temporomandibular Joint in Juvenile Idiopathic Arthritis

Abstract: HBF within the TMJ is relatively common in patients with JIA receiving IAC injections for TMJ arthritis. Future prospective studies are required to delineate the risks posed by the injections themselves as opposed to the underlying disease activity, as well as to evaluate alternative forms of local therapy to the TMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 27 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…IAGCs may alleviate joint symptoms and help restore function. This recommendation is conditional, as there have been unique TMJ‐specific serious adverse events, including heterotopic ossification and impaired growth (52–55). Therefore, IAGCs for TMJ arthritis should be used sparingly for symptomatic children, preferably those who are skeletally mature (53–56).…”
Section: Results/recommendationsmentioning
confidence: 99%
“…IAGCs may alleviate joint symptoms and help restore function. This recommendation is conditional, as there have been unique TMJ‐specific serious adverse events, including heterotopic ossification and impaired growth (52–55). Therefore, IAGCs for TMJ arthritis should be used sparingly for symptomatic children, preferably those who are skeletally mature (53–56).…”
Section: Results/recommendationsmentioning
confidence: 99%
“…In the present issue of The Journal, Stoll, et al 15 found that 14% developed HBF after TMJ IACI in a retrospective study of 238 children. In this study, nonresponders to TMJ IACI received intraarticular TMJ injections with infliximab.…”
mentioning
confidence: 76%
“…Some drugs, such as corticosteroids, when administered by intra-articular injection, are also possible causes of heterotopic TMJ calcifications. 26,27 It is worth noting that the majority of previous studies involving TMJ calcifications were limited to cases of synovial chondromatosis. It was not an aim of the present study to determine the causal factors and/or to diagnose the TMJ calcifications precisely, since the data available were limited to the CBCT images, with no access to any additional information or clinical examination data.…”
Section: Discussionmentioning
confidence: 99%